Pengembangan Media Pembelajaran E-Poster pada Pembelajaran IPAS Kelas IV Sekolah Dasar - Siswanto, Argi Eko; Asrial, Asrial; Alirmansyah, Alirmansyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to determine the conceptual and procedural feasibility of developing e-Poster learning media in class IV science and science learning at SDN 111/I Muara Bulian for the 2023/2024 academic year. This media development research uses the DDD-E (Decide, Design, Develop, Evaluate) development model. Research data was obtained from material validation, media validation, and language validation as well as from teacher response questionnaires and student responses. The results of the research show that the development of e-Poster learning media in science and science learning in grade IV elementary schools is conceptually and procedurally suitable for use and practical in the learning process in elementary schools.